Dimensionamento de um túnel de vento subsônico - Lins, Davi Ribeiro (2018)
The Laboratory of Aerodynamics and Fluid Mechanics of the Federal University of Ceará uses the wind tunnel as a tool in the study of flows in objects and in the validation of computational simulations. Current research lines require a wind tunnel that reaches speeds higher than currently attained. The objective of this work was to design a new wind tunnel, calculate its total pressure loss, estimate the power required for the fan and evaluate the final result of the project with a computational simulation. Each part of the wind tunnel, including test section, contraction nozzle, diffuser and settling chamber, was sized and calculated its pressure loss. The final result was a wind tunnel of 5.87 meters in length, with a test section of square section area of 0.25 m² and velocity of 30 m/s. The total pressure loss calculated was 173.2 Pascal and the estimated fan power was 3 cv. A computational simulation to evaluate the design was made disregarding the effects of the settling chamber, which results in a lower loss of total pressure in the wind tunnel. The results of the simulation presented high divergences in relation to the calculated values in the section of tests in the order of 10% for the speed and 20% for the dynamic pressure. According to the graphs provided by the simulation the velocity, the dynamic pressure and the static pressure behaved as expected along the wind tunnel. Despite the appearance of a small turbulence, it was verified that there is no separation of the flow and no counterflow on the walls of the diffuser. These simulation results show that the wind tunnel met the initial expectations of the project.